2019
DOI: 10.1016/j.jhep.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pathways in alcoholic steatohepatitis

Abstract: Inflammatory processes are primary contributors to the development and progression of alcoholic steatohepatitis (ASH), with severe alcoholic hepatitis characterised by non-resolving inflammation. Inflammation in the progression of ASH is a complex response to microbial dysbiosis, loss of barrier integrity in the intestine, hepatocellular stress and death, as well as inter-organ crosstalk. Herein, we review the roles of multiple cell types that are involved in inflammation in ASH, including resident macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
300
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 278 publications
(307 citation statements)
references
References 107 publications
1
300
1
5
Order By: Relevance
“…In this study, we systematically profiled 18 sICPs in the plasma samples from a large cohort of patients with AH, HDCs, and HCs. In line with profound immune dysregulation in patients with AH, (3,19) we found that 17 out of 18 sICPs examined here were dysregulated (six up-regulated and 11 down-regulated). A previous study found that the TIM-3 ligand galectin-9 was elevated in patients with AH.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In this study, we systematically profiled 18 sICPs in the plasma samples from a large cohort of patients with AH, HDCs, and HCs. In line with profound immune dysregulation in patients with AH, (3,19) we found that 17 out of 18 sICPs examined here were dysregulated (six up-regulated and 11 down-regulated). A previous study found that the TIM-3 ligand galectin-9 was elevated in patients with AH.…”
Section: Discussionsupporting
confidence: 82%
“…Alcoholic hepatitis (AH) is a severe inflammatory liver disease that develops in 10%‐35% of chronic heavy drinkers. Although the exact trigger for development of AH is still unclear, alcohol‐induced translocation of gut bacteria and bacterial components into the liver and blood and subsequent activation of liver‐resident macrophages (Kupffer cells) and other immune and nonimmune cells play a critical role in the initiation and progression of AH . Patients with AH have elevated levels of a wide range of proinflammatory factors, such as interleukin‐8 (IL‐8) and tumor necrosis factor alpha (TNF‐α), and their immune cells are highly dysregulated, which is characterized by immune hyperactivation, exhaustion, and dysfunction …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Wei Zhong, 1,2 Xiaoyuan Wei, 3 Liuyi Hao, 1 Tai-Du Lin, 1,4 Ruichao Yue, 1 Xinguo Sun, 1 Wei Guo, 1 Haibo Dong, 1 Tianjiao Li, 2 Ali R. Ahmadi, 5 Zhaoli Sun, 5 Qibin Zhang, 1,4 Jiangchao Zhao, 3…”
Section: Paneth Cell Dysfunction Mediates Alcohol-related Steatohepatmentioning
confidence: 99%